Insights into Fibrinogen-Mediated COVID-19 Hypercoagubility in Critically Ill Patients. Issue 1 (20th January 2022) - Miltiades, Andrea; Houck, Philipp J.; Monteleone, Matthew; Harrison, Neil L.; Cabrera-Garcia, David; Roh, David; Wagener, Gebhard
Abstract : Coronavirus disease-2019 (COVID-19) is associated with hypercoagulability that may cause thromobembolic complications. We describe our recent studies investigating the mechanisms of hypercoagulability in patients with severe COVID-19 requiring mechanical ventilation during the COVID-19 crisis in New York City in spring 2020. Using rotational thombelastometry we found that almost all patients with severe COVID-19 had signs of hypercoagulability compared with non–COVID-19 controls. Specifically, the maximal clot firmness in the fibrin-based extrinsically activated test was almost twice the upper limit of normal in COVID patients, indicating a fibrin-mediated cause for hypercoagulability. To better understand the mechanism of this hypercoagulability we measured the components of the fibrinolytic pathways. Fibrinogen, tissue plasminogen activator and plasminogen activator inhibitor-1, but not plasminogen levels were elevated in patients with severe COVID-19. Our studies indicate that hypercoagulability in COVID-19 may be because of decreased fibrinolysis resulting from inhibition of plasmin through high levels of plasminogen activator inhibitor-1. Clinicians creating treatment protocols for anticoagulation in critically ill COVID-19 patients should consider these potential mechanisms of hypercoaguability.